Застосування технології ml.net задля автоматичного сортування та тегування текстових документів для семантичної цифрової бібліотеки. - Заворіна, М. А. (ХНУРЕ, 2024)
The paper proposes to develop a tool that will allow creating a semantic network of files in addition to the standard hierarchical Windows file system, which could automatically sort text files for a semantic digital library by categories based on their content. The preparation of a corpus of texts for the purpose of automatically obtaining categories, tags and attributes to fill a semantic digital library is an extremely important and relevant technology. In order to implement such an add-on to the Semantic File System, it is proposed to apply ML.NET technology, this will allow easy integration with other ML.NET components or external libraries, expanding the possibilities of sorting text documents.
Keywords: ML.NET; Semantic; тегування тексту; автоматичне сортування